Răspuns :
3*{10+2*[40-2*(28-3*5)]}-7x=51
3*{10+2*[40-2*(28-15)]}-7x=51
3*{10+2*[40-2*13]}-7x=51
3*{10+2*[40-26]}-7x=51
3*(10+2*14)-7x=51
3*(10+28)-7x=51
3*38-7x=51
114-7x=51
7x=114-51
7x=63
x=63:7
x=9
3*{10+2*[40-2*(28-15)]}-7x=51
3*{10+2*[40-2*13]}-7x=51
3*{10+2*[40-26]}-7x=51
3*(10+2*14)-7x=51
3*(10+28)-7x=51
3*38-7x=51
114-7x=51
7x=114-51
7x=63
x=63:7
x=9
3*{10+2*[40-2*(28-15)]}-7x=51
3*{10+2*[40-2*13]}-7x=51
3*{10+2*[40-26]}-7x=51
3*{10+2*14}-7x=51
3*{10+28}-7x=51
3*38-7x=51
114-51=7x
63=7x
x=63/7
x=9
3*{10+2*[40-2*13]}-7x=51
3*{10+2*[40-26]}-7x=51
3*{10+2*14}-7x=51
3*{10+28}-7x=51
3*38-7x=51
114-51=7x
63=7x
x=63/7
x=9